빛에 반응하는 타이포그래피 형상에 관한 연구 - 전은선; Jeon Eoun Sun; 김성계; Kim Sung Kye (기초조형학연구, 2019)
인간의 삶에 있어 중추적 역할을 해온 빛과 문자는 언어 의미 전달뿐만 아니라 시각예술로서 사회, 문화, 기술 그리고 매체의 영향을 받으며 발전되어 왔고, 시간적·공간적 표현 수단으로 다양한 디자인 개발과 활용이 꾸준히 발현되어　왔다. 이에 본 논문은 빛의 방향에 따라 다르게 나타나는 타이포그래피 형상에 대해 시각적 감성의 차이를 실증적으로 연구 분석하고, 더욱 가속화된 과학 기술과 함께 발전해 나가는 타이포그래피에 대한 사고영역의 확장과 타이포그래피 형상 변화의 기초 자료로 사용될 것을 기대한다. 본 연구 실험에서는 제한된 인공광의 흐름을 통하여 만들어진 타이포그래피 형상이 어떤 심리적 기제를 가지는가에 목적을 두고 관련된 선행연구 및 서적을 중심으로 이론적 바탕과 기준을 마련하고, 심리적 활용 방안을 다음과 같이 모색하였다. 첫째, 광량 0에서는 형용사의 평균점수가 4점 근처에 포진하였고, 광량 +1에서는 평균점수의 범위가 넓게 나타나는 것으로 보아, 광량 0보다는 광량 +1에서 감성이 더욱 명확하게 나타남을 알 수 있었다.　둘째, 평면보다는 입체 타이포그래피에서 감성이 더욱 명확하게 나타남을 알 수 있었다. 셋째, 빛의 방향에 따른 이미지 차이로는 측면광, 역광에서는 흰, 안정된, 밝은, 실용적인의 감성이 나타났으며, 정면광, 탑광에서는 검은, 불안정한, 어두운, 비실용적인의 감성이 나타나 방향별 이미지의 차이가 있음을 알 수 있었다. 본 연구에서는 빛에 반응하는 타이포그래피가 어떠한 형상을 가지는지, 그 형상이 어떠한 심리 기제를 가지는지 규명하였고, 필요한 제작 방법론에 있어서도 많은 지견을 얻었다. 그러나 설문과정에서 사용된 타이포그래피의 샘플을 한정하여 결과를 일반화 하는데 한계를 가진다. 따라서 위의 사항들을 고려하여 연구하면 더욱 다양한 평가와 명확한 결론을 도출해 낼수 있는 좋은 자료가 될 것이라 생각된다. Light and characters have played a pivotal role in human life and have been developed with the influence of society, culture, technology and media not only as means of conveying language but also as visual arts, being utilized and developed over time as methods of time and spacial expression. In this paper, we empirically analyze the differences in visual sensibility of different typefaces according to the direction of light. It is anticipated that the results of this study will be a useful resource for understanding the changes in typographical form as well as the ever expanding scope of thought of typography. The purpose of this study is to find out the psychological mechanism generated by the flow of limited artificial light onto a typographical form, to establish the theoretical background and criteria based on related studies and books and to explore the psychological utilization plan. The results are as follows. First, the average score of the adjective was about 4 at the intensity of 0, but resulted in a larger spread at the intensity of +1. Therefore, it can be seen that the sensitivity is more marked at a light intensity of +1 than of 0. Second, it was observed that emotions were more evident in three-dimensional typographic forms than flat-panel ones. Third, the difference in the image perception according to the direction of the light showed "white," "stable," and "practical" in the side lights and backlight, and "black," "unstable," "dark," and "impractical" in the front light and the top light. In this study, we have clarified what type of typography responds to light, what type of psychological mechanism is needed for the shape, and expanded the knowledge about the required production methodology. However, by limiting the sample of typographic forms used in the survey process, the generalization of the results is also limited. Therefore, it is anticipated that addition research that takes these results into account will result in even more promising findings.